Analysis of the gut contents of narrow-lined puffer, Arothron manilensis (de Proce, 1822) in Conception, Iloilo. - Jazon, Deric Louis A. (2017.)
Tetraodontis are characterized by a hard skin that is usually enveloped with small spinulous scales, absence of pelvic fins, no fin spines, a single often short-based dorsal fin, a single often short based anal fin and absence of ribs. Although tetraodontids are not economically important in the Philippines, Japan considers it as a delicacy and some countries utilize it as a component of a marine aquarium trade, and Arothron manilensis is a member of this family. This family was conducted to analyze the gut contents of Arothron manilensis and to determine if there are any shift in their diet using samples from trawl net catches sampled in September 2011 to January 2012 in Conception, Iloilo. Eighty-eight fish samples were characterized into five size classes using an interval of 0.5cm: 3.5-3.9 cm, 4.0-4.4 cm, 4.5-4.9 cm, and 5.5 -5-9 cm. Guts were then emptied in a Petri dish with its contents spread out evenly to determine % chime by estimation and to examine its contents using a dissecting microscope. Non-chyme components were identified and quantified up to the lowest possible level. The results revealed difference in the percent chime and non-chyme component. The chime component was inversely proportional with respect to the fish size. Moreover, prey items were more diverse in smaller fishes in relation to larger fishes in terms of their standard lengths. Arothron manilensis primarily feed on benthic organisms like gastropods, bivalves and forams though during their early stages, they feed on isopods, ostracods and amphipods. They can be considered as specialist when they grow in size since they have a small range of prey items which was exhibited in the guts of larger species.
Special Problem (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo
Keywords: Arothron manilensis; Gut contents; Gut contents analysis; ontogenetic shift; prey items